PERLINDUNGAN HUKUM TERHADAP HAK ASASI SEORANG WANITA/PEREMPUAN DALAM HUKUM POSITIF DI INDONESIA - Susrama, I Nengah (Jurnal Advokasi, 2017)
Although the Indonesian nation today has a set of rules of law including the court of human rights, but in reality in the daily lives of people in the community, we often hear and see violations and crimes against human rights, especially those affected and experienced by the people Lady. Perhaps this is due to an assumption in the community that women are physically weak and are considered second class citizens in community life. Human rights for women already have sufficient legal protection in Indonesian legislation, both in general and special law.